An asymmetric nanogap electrode and a method for preparing the same

CN122930657APending Publication Date: 2026-10-16SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611418149.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明第一方面的一个目的在于提供一种非对称纳米间隙电极的制备方法,解决现有技术中纳米间隙电极制备过程依赖高精度光刻、刻蚀、击穿或沉积监控等工艺,导致纳米间隙尺寸可控性差、结构一致性不足且难以兼顾低成本和大面积制备适应性的技术问题

Benefits of technology

[0015] This application utilizes a predetermined surface energy difference or adsorption energy difference between the first electrode structure and the substrate to induce organic molecular materials to migrate and accumulate around the first electrode structure at a predetermined temperature, forming a selected organic molecular structure with a predetermined lateral expansion size. This selected structure serves as a sacrificial confinement template during the deposition of the second electrode layer, thus establishing a synergistic preparation mechanism of selective growth defining gaps and sacrificial removal forming gaps. Based on this mechanism, the width of the nanogap can be controlled within the range of 10nm-100nm by parameters such as the type of organic molecule, substrate temperature, deposition rate, deposition time, equivalent deposition thickness, and surface energy difference or adsorption energy difference, without being limited by the length of a single molecular chain or a fixed gap layer thickness. Simultaneously, the selected organic molecular structure has an actual physical thickness, which can form a spatial barrier to the first electrode structure during the deposition of the second electrode layer, reducing the risk of bridging and short-circuiting. It can also be removed under the action of a good solvent and ultrasonic treatment, causing the second electrode layer on its surface to detach along with it, while the second electrode layer on the substrate surface remains as the second electrode structure. This improves the boundary clarity, size consistency, structural integrity, and preparation yield of the nanogap. Furthermore, the selective growth process does not rely on specific chemical bonding between a specific head base and a specific metal, and can be achieved through vacuum thermal evaporation or physical vapor deposition, which helps to shorten the process time, reduce pollution and defects caused by wet processing, and improve material compatibility and adaptability to large-area preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930657A_ABST
    Figure CN122930657A_ABST
Patent Text Reader

Abstract

The application discloses an asymmetric nanogap electrode and a preparation method thereof, and relates to the technical field of micro-nano processing. The preparation method comprises the following steps: forming a first electrode layer comprising a plurality of first electrode structures arranged at intervals on a substrate; regulating the substrate to a preset temperature and keeping the substrate, and depositing an organic molecular material on the surface of the substrate and the first electrode layer to form an organic molecular selected-area structure on the periphery of each first electrode structure; depositing a second electrode layer on the surface of the substrate and the organic molecular selected-area structure; and removing the second electrode layer and the organic molecular selected-area structure on the surface of the organic molecular selected-area structure by ultrasonic treatment to form the asymmetric nanogap electrode. The organic molecular selected-area structure is used as a sacrifice limited template to limit the interval between the first electrode structure and the second electrode structure, so that the self-alignment and controllable preparation of the asymmetric nanogap electrode are realized, and the size consistency of the nanogap is improved, the process cost is reduced, and the preparation adaptability of a large area is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of micro-nano fabrication technology, specifically to an asymmetric nano gap electrode and its fabrication method. Background Technology

[0002] Nanogap electrodes typically refer to spaced structures with dimensions at the nanoscale. They usually consist of two or more metal electrodes spaced apart from each other, with the spacing between the electrodes ranging from 1 nm to 100 nm. Because nanogap electrodes can form localized electric fields, tunneling channels, or molecular-scale detection regions at extremely small scales, they can be applied to micro / nano devices such as molecular devices, sensors, optoelectronic devices, enhanced Raman scattering detection structures, diodes, and transistors.

[0003] Existing methods for fabricating nanogap electrodes mainly include electron beam lithography, focused ion beam processing, nanoimprinting, scanning probe fabrication, electromigration breakdown, shadow mask deposition, electrochemical deposition, adhesion lithography, and atomic layer lithography. While electron beam lithography and focused ion beam processing can achieve high resolution, they are typically sequential processes, resulting in slow fabrication speeds and high equipment costs, making them unsuitable for large-area fabrication. Nanoimprinting, although offering some scale-up capabilities, suffers from mold roughness and feature size that can easily transfer to subsequent structures, affecting the edge quality and dimensional consistency of the nanogap. Electromigration breakdown relies on current-induced localized fracture processes, leading to unpredictable electrode separation positions and gap sizes. Electrochemical deposition typically requires real-time monitoring of the deposition process to prevent gap closure. While adhesion lithography and atomic layer lithography can be used to construct nanogap electrodes, they still face challenges such as difficulty in controlling gap sizes, slow processing steps, and high complexity.

[0004] Therefore, existing nano-gap electrode fabrication technologies often struggle to achieve a good balance between fabrication cost, process efficiency, size controllability, structural consistency, and large-area fabrication capability. Especially when fabricating nano-gap electrodes with widths of 10nm-100nm, relying solely on photolithography precision, etching precision, breakdown process, deposition monitoring, or template replication precision to define the nano-gap can easily lead to problems such as high process costs, complex procedures, large fluctuations in nano-gap size, insufficient boundary consistency, or difficulty in achieving self-aligned fabrication. Summary of the Invention

[0005] One objective of the first aspect of this invention is to provide a method for fabricating asymmetric nanogap electrodes, thereby solving the technical problems in the prior art where the fabrication process of nanogap electrodes relies on high-precision photolithography, etching, breakdown, or deposition monitoring, resulting in poor controllability of nanogap size, insufficient structural consistency, and difficulty in balancing low cost and large-area fabrication adaptability.

[0006] Another objective of the first aspect of this invention is to improve the formation stability and boundary clarity of the selected region structure of organic molecules.

[0007] The second aspect of this invention aims to provide an asymmetric nanogap electrode prepared according to the above-described preparation method.

[0008] According to a first aspect of the present invention, the present invention provides a method for preparing an asymmetric nanogap electrode, comprising the following steps: A first electrode layer having multiple spaced first electrode structures is formed on a substrate, wherein each first electrode structure has a preset surface energy difference or a preset adsorption energy difference with the substrate surface. An organic molecule selected region structure with a preset lateral expansion size is formed on the periphery of the first electrode structure. The organic molecule selected region structure is formed by the migration and enrichment of organic molecule material deposited on the substrate surface to the periphery of the first electrode structure when the substrate is at a preset temperature. A second electrode layer is deposited on the surface of the substrate and the organic molecule selected region structure, the material of the second electrode layer being different from that of the first electrode layer; The second electrode layer and the organic molecule selected region structure on the surface of the organic molecule selected region structure are removed to form a nano gap between the second electrode structure and the first electrode structure, thereby preparing the asymmetric nano gap electrode with a nano gap width of 10nm-100nm. The second electrode structure is the portion of the second electrode layer located between the organic molecule selected region structures.

[0009] Optionally, the preset surface energy difference is 0.7 J / m. 2 -1.3J / m 2 Any value among them.

[0010] Optionally, the organic molecule has at least one of a non-planar molecular structure, a predetermined surface migration capability, or a predetermined wettability, and the adsorption stability or wettability of the organic molecule on the surface of the first electrode structure is higher than its adsorption stability or wettability on the substrate surface.

[0011] Optionally, the preset temperature of the substrate is any value between 30℃ and 250℃.

[0012] Optionally, the deposition rate of the organic molecules is any value between 0.01 nm / min and 10 nm / min.

[0013] Optionally, the step of depositing a second electrode layer on the surface of the substrate and the organic molecule selected region structure further includes: The substrate and / or the organic molecule selected region structure are pretreated, and the pretreatment includes at least one of surface cleaning treatment, plasma treatment, surface activation treatment or interface modification treatment.

[0014] According to a second aspect of the present invention, the present invention also provides an asymmetric nanogap electrode prepared by the method described in any one of the above claims.

[0015] This application utilizes a predetermined surface energy difference or adsorption energy difference between the first electrode structure and the substrate to induce organic molecular materials to migrate and accumulate around the first electrode structure at a predetermined temperature, forming a selected organic molecular structure with a predetermined lateral expansion size. This selected structure serves as a sacrificial confinement template during the deposition of the second electrode layer, thus establishing a synergistic preparation mechanism of selective growth defining gaps and sacrificial removal forming gaps. Based on this mechanism, the width of the nanogap can be controlled within the range of 10nm-100nm by parameters such as the type of organic molecule, substrate temperature, deposition rate, deposition time, equivalent deposition thickness, and surface energy difference or adsorption energy difference, without being limited by the length of a single molecular chain or a fixed gap layer thickness. Simultaneously, the selected organic molecular structure has an actual physical thickness, which can form a spatial barrier to the first electrode structure during the deposition of the second electrode layer, reducing the risk of bridging and short-circuiting. It can also be removed under the action of a good solvent and ultrasonic treatment, causing the second electrode layer on its surface to detach along with it, while the second electrode layer on the substrate surface remains as the second electrode structure. This improves the boundary clarity, size consistency, structural integrity, and preparation yield of the nanogap. Furthermore, the selective growth process does not rely on specific chemical bonding between a specific head base and a specific metal, and can be achieved through vacuum thermal evaporation or physical vapor deposition, which helps to shorten the process time, reduce pollution and defects caused by wet processing, and improve material compatibility and adaptability to large-area preparation.

[0016] Furthermore, the preset surface energy difference of the present invention is 0.7 J / m. 2 -1.3J / m 2 By controlling the surface energy difference between the first electrode layer and the substrate within the above range, organic molecules can exhibit significantly different interfacial adsorption, wetting, and migration behaviors on the surface of the first electrode layer and the surface of the substrate. This makes organic molecules more inclined to migrate, adsorb, nucleate, or accumulate on the periphery of the first electrode structure with higher surface energy during the deposition process, rather than forming a non-selective continuous deposition layer on the substrate surface. This improves the formation stability and boundary clarity of the selected organic molecule structure.

[0017] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description

[0018] The following sections will describe some specific embodiments of the invention in detail by way of example and not limitation, with reference to the accompanying drawings. The same reference numerals in the drawings denote the same or similar parts or portions. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings: Figure 1 This is a schematic process flow diagram of a method for preparing an asymmetric nanogap electrode according to an embodiment of the present invention; Figure 2 This is a schematic structural flowchart of a method for preparing an asymmetric nanogap electrode according to an embodiment of the present invention; Figure 3 This is a scanning electron microscope image of a substrate after molecular selective region growth according to an embodiment of the present invention; Figure 4 This is a scanning electron microscope image of the product obtained in step S100 of preparing the asymmetric nanogap electrode according to Example 1 of the present invention; Figure 5 This is a scanning electron microscope image of the product obtained in step S200 of preparing the asymmetric nanogap electrode according to Example 1 of the present invention; Figure 6 This is a scanning electron microscope image of the product obtained in step S300 of the preparation of asymmetric nanogap electrodes according to Example 1 of the present invention; Figure 7 This is a scanning electron microscope image of the product obtained in step S400 of the preparation of asymmetric nanogap electrodes according to Example 1 of the present invention; Figure 8 This is a partially enlarged scanning electron microscope image of the second electrode layer after deposition according to Embodiment 1 of the present invention; Figure 9 This is an atomic force microscopy test image of the selected region structure of an organic molecule according to Embodiment 2 of the present invention; Figure 10 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 1 of the present invention. Figure 11 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 2 of the present invention; Figure 12 This is an atomic force microscopy test image of the selected region structure of an organic molecule according to Example 3 of the present invention; Figure 13 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 3 of the present invention; Figure 14 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 4 of the present invention. Figure 15This is a scanning electron microscope image of the circular nano-gap electrode array prepared according to Example 4 of the present invention.

[0019] Figure label: 100 - Asymmetric nanogap electrode, 10 - Substrate, 20 - First electrode layer, 21 - First electrode structure, 30 - Selected region structure of organic molecules, 40 - Second electrode layer, 42 - Second electrode structure, 50 - Nanogap. Detailed Implementation

[0020] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and are not intended to limit the scope of the invention.

[0021] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, it should be noted that, for ease of description, only the parts relevant to this application are shown in the accompanying drawings, not the entire structure. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application.

[0022] The terms “comprising” and “having”, and any variations thereof, used in this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not limited to the steps or units listed, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to such process, method, product, or apparatus.

[0023] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0024] Figure 1 This is a schematic process flow diagram illustrating a method for fabricating an asymmetric nano-gap electrode according to an embodiment of the present invention. Figure 2 This is a schematic structural flowchart of a method for fabricating an asymmetric nano-gap electrode according to an embodiment of the present invention. Figure 3 This is a scanning electron microscope image of a substrate after molecular selective region growth according to an embodiment of the present invention.

[0025] like Figure 1 and Figure 2 As shown, the present invention provides a method for preparing an asymmetric nano-gap electrode 100, comprising the following steps: Step S100: A first electrode layer 20 having a plurality of spaced first electrode structures 21 is formed on the substrate 10. Each first electrode structure 21 has a preset surface energy difference or a preset adsorption energy difference with the surface of the substrate 10. The lateral dimension of the first electrode structure 21 is referenced. Figure 3 The spacing L2 in the middle; Step S200: An organic molecule selected region structure 30 with a predetermined lateral expansion size is formed on the periphery of the first electrode structure 21. The organic molecule selected region structure 30 is formed by the migration and enrichment of organic molecule material deposited on the surface of the substrate 10 to the periphery of the first electrode structure 21 when the substrate 10 is at a predetermined temperature. The lateral size of the organic molecule selected region structure 30 is referenced to... Figure 3 The spacing L1 in the middle; Step S300: Deposit a second electrode layer 40 on the surface of the substrate 10 and the organic molecule selected region structure 30; Step S400: Remove the second electrode layer 40 and the organic molecule selected region structure 30 from the surface of the organic molecule selected region structure 30 to form a nano gap 50 between the second electrode structure 42 and the first electrode structure 21 (refer to...). Figure 3 The asymmetric nanogap electrode 100 with a nanogap 50 width of 10 nm to 100 nm is prepared by spacing L3 in the second electrode layer 40. The second electrode structure 42 is the portion of the second electrode layer 40 located between the organic molecule selected region structures 30. Here, the preparation method of this application can prepare nanogap 50 with a width of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, or any value in the range of 10 nm to 100 nm.

[0026] In this embodiment, the mechanism by which the organic molecular selected region structure 30 regulates the width of the nano-gap is a phased correspondence between the amount of organic molecule deposition and the lateral expansion behavior of the selected region structure. Specifically, in the unsaturated stage of organic molecule deposition, organic molecules preferentially migrate, adsorb, and accumulate around the first electrode structure 21. At this time, the three-phase contact line of the organic molecular selected region structure 30 is mainly pinned by the edge of the first electrode structure 21. As the amount of organic molecule deposition increases, the selected region structure mainly accumulates and grows along the thickness direction or the vertical direction. Its contact angle has not yet reached the saturation equilibrium value or the maximum advancing contact angle. Therefore, the lateral expansion size of the organic molecular selected region structure 30 remains basically stable, and the corresponding nano-gap size changes little. When the amount of organic molecule deposition continues to increase and reaches the saturation stage, the contact angle between the organic molecular selected region structure 30 and the substrate 10 reaches the saturation equilibrium value or the maximum advancing contact angle. After this, the organic molecules that continue to be deposited can hardly maintain a stable interface morphology by simply stacking in the vertical direction. The three-phase contact line unpinns and moves outward, causing the organic molecular selected region structure 30 to expand laterally along the surface of the substrate 10. Therefore, this application can adjust the lateral expansion size of the organic molecule selected region structure 30 by controlling parameters such as the amount of organic molecule deposition, deposition rate, deposition time, and substrate preset temperature, and further convert the lateral expansion size into the nano gap width between the first electrode structure 21 and the second electrode structure 42, thereby achieving controllable adjustment of the nano gap size.

[0027] In this embodiment, by utilizing the preset surface energy difference or preset adsorption energy difference between the first electrode structure 21 and the substrate 10, organic molecular materials are induced to migrate and accumulate around the first electrode structure 21 at a preset temperature, forming an organic molecular selected region structure 30 with a preset lateral expansion size. This organic molecular selected region structure 30 is then used as a sacrificial confinement template in the subsequent deposition process of the second electrode layer 40, thereby forming a synergistic mechanism based on interface energy difference-induced selected region growth, lateral expansion size-defined gaps, and sacrificial removal to form gaps. This mechanism can transform the thermodynamic migration, kinetic nucleation, and interface enrichment behavior of organic molecules into a means of defining the size of the nano-gap 50, allowing the width of the nano-gap 50 to be controlled within the range of 10nm-100nm. Simultaneously, the organic molecular selected region structure 30 has an actual physical thickness, which can form a spatial barrier to the first electrode structure 21 during the deposition of the second electrode layer 40, reducing the risk of short circuits caused by the second electrode layer 40 crossing or penetrating the edge of the first electrode structure 21, thereby improving the boundary clarity, size consistency, and structural reliability of the nano-gap 50.

[0028] Furthermore, this application combines high preparation efficiency with a large window for controlling the size of the nano-gap 50. Specifically, the organic molecule selected region structure 30 can be formed by vacuum thermal evaporation or physical vapor deposition, and its growth state can be controlled by parameters such as substrate temperature 10, deposition rate, deposition time, and equivalent deposition thickness. Compared with long-term liquid-phase modification or monolayer self-assembly processes, this can shorten the formation time of the protective / confined structure and reduce contamination, defects, and process fluctuations caused by long-term solution immersion. At the same time, the lateral expansion size of the organic molecule selected region structure 30 can also be adjusted by factors such as the type of organic molecule, the preset temperature of the substrate 10, deposition rate, deposition time, equivalent deposition thickness, and surface energy difference or adsorption energy difference. This allows this application to prepare nano-gap 50s with widths of 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, or 100nm, or nano-gap 50s with any width in the range of 10nm-100nm. Therefore, the size of the nano gap 50 in this application is not limited by the length of a single molecular chain or the thickness of a fixed inorganic gap layer, but is adjusted by the growth boundary of the organic molecular selected region structure 30. While improving the preparation efficiency, it can meet the differentiated requirements of the nano gap 50 size for different application scenarios such as sensors, molecular devices, and optoelectronic devices.

[0029] Furthermore, this application exhibits good material adaptability and structure retention. Specifically, the selective growth of organic molecules in this application does not require organic molecules to rely on specific head groups to form specific chemical bonds with specific metals. Instead, it utilizes the surface energy difference, adsorption energy difference, wettability difference, or nucleation barrier difference between the first electrode structure 21 and the substrate 10 to allow organic molecules to selectively migrate and accumulate around the first electrode structure 21. Therefore, the first electrode material, the second electrode material, the substrate 10 material, and the organic molecule material can be selected according to different device requirements. Moreover, when the first electrode layer 20 and the second electrode layer 40 are made of different materials, asymmetric physicochemical boundaries with different work functions, electrochemical activities, catalytic activities, or molecular adsorption characteristics can be formed on both sides of the nano-gap 50, thereby providing a structural basis for gas sensing, molecular recognition, electrochemical response, or rectification devices. Meanwhile, the organic molecular selected region structure 30 plays a spatial isolation role during the deposition of the second electrode layer 40, and can be dissolved, swollen or softened under the action of subsequent good solvent and ultrasonic treatment, so that the second electrode layer 40 on its surface loses support and is removed along with the organic molecular selected region structure 30, while the second electrode layer 40 deposited on the surface of the substrate 10 is partially retained and forms the second electrode structure 42. This reduces the risk of large-area mechanical peeling causing damage to the edge of the nanoelectrode, improves the integrity of the second electrode structure 42 and the clarity of the boundary of the nano gap 50.

[0030] In step S200, the substrate 10 with the first electrode layer 20 is adjusted to a preset temperature, and organic molecular materials are deposited at this preset temperature according to preset deposition parameters. This allows organic molecules to selectively migrate, adsorb, nucleate, or accumulate on the periphery of the first electrode structure 21 under the influence of the interfacial difference between the first electrode structure 21 and the substrate 10, thereby forming organic molecular selective region structures 30 with a preset lateral expansion size on the periphery of each first electrode structure 21. Here, the interfacial difference refers to the fact that the adsorption capacity of the first electrode structure 21 for organic molecular materials is greater than that of the substrate 10; that is, there is a preset surface energy difference or preset adsorption energy difference between the surfaces of each first electrode structure 21 and the substrate 10, so that the adsorption capacity of the first electrode structure 21 for organic molecular materials is greater than that of the substrate 10.

[0031] In this embodiment, the first electrode structure 21 is not only used to form one side electrode of the asymmetric nanogap electrode 100, but also serves as an interface induction benchmark for the selective growth of organic molecules, enabling organic molecules to selectively migrate, adsorb, nucleate, or accumulate around the first electrode structure 21. The organic molecule selective region structure 30 serves as a sacrificial confinement template that defines the deposition boundary of the second electrode layer 40 and the width of the nanogap 50. Under the spatial barrier effect of the sacrificial confinement template, the second electrode layer 40 forms a second electrode structure 42 that is self-aligned and separated from the first electrode structure 21. In other words, this application forms a continuous and synergistic preparation process in which the first electrode structure 21 induces the selective growth of organic molecules, the organic molecule selective region structure 30 defines the gap size, the second electrode layer 40 is deposited to form the second electrode structure 42, and the sacrificial template is removed to form the nanogap 50. This allows the size and position of the nanogap 50 to be controlled by the lateral expansion size of the organic molecule selective region structure 30, thereby improving the size controllability, structural consistency, and large-area fabrication adaptability of the asymmetric nanogap electrode 100.

[0032] In this embodiment, by utilizing the differences in interfacial behavior of organic molecules on different material surfaces, they are selectively enriched around the first electrode structure 21 at a preset temperature and deposition rate. This organic molecule-rich region serves as a sacrificial confinement structure in the subsequent metal deposition process. Specifically, when organic molecules are deposited onto the surfaces of the substrate 10 and the first electrode layer 20, they exhibit different adsorption energies, wettability, or interfacial free energies between the surface of the first electrode structure 21 and the surface of the substrate 10. By controlling the temperature of the substrate 10, the organic molecules can acquire appropriate surface diffusion capabilities: in non-target areas, organic molecules are more likely to desorb, migrate, or flow; around the first electrode structure 21, organic molecules are more likely to be adsorbed, pinned, nucleated, or enriched. Therefore, organic molecules do not form a uniform continuous film across the entire surface of the substrate 10, but rather preferentially form a selected region structure around the first electrode structure 21.

[0033] In some embodiments, the organic molecules are organic molecules capable of selective migration, adsorption, nucleation, or enrichment at a preset temperature. Specifically, the organic molecule material is at least one of a non-planar molecular structure, a preset surface migration capability, or a preset wettability, and the adsorption stability or wettability of the organic molecules on the surface of the first electrode structure 21 is higher than that on the surface of the substrate 10. By selecting the above-mentioned organic molecules, under the influence of differences in interfacial interactions, adsorption energy, or wettability between the first electrode structure 21 and the substrate 10, the organic molecules can selectively migrate to the periphery of the first electrode structure 21 and form an organic molecule selective region structure 30, while being able to be removed during subsequent ultrasonic treatment or solvent-assisted treatment, thereby enabling the organic molecule selective region structure 30 to serve as both a selective growth template and a sacrificial removal template.

[0034] In this embodiment, the patterning process for the first electrode layer 20 includes one or more of photolithography, nanoimprinting, shadow mask deposition, and etching. Specifically, a photoresist layer or imprinted resist layer with a preset pattern can be formed on the surface of the substrate 10 first, and then the first electrode layer 20 can be deposited on the surface of the substrate 10. Subsequently, the photoresist layer or imprinted resist layer is removed to retain the patterned first electrode layer 20 on the surface of the substrate 10, thereby forming the first electrode layer 20.

[0035] In one specific embodiment, the patterning process includes spin-coating photoresist, pre-baking, exposure, development, metal deposition, and lift-off. Through these processes, multiple spaced stripe-like, island-like, line-like, interdigitated, or array-like first electrode structures 21 can be formed on the surface of the substrate 10. The morphology, width, spacing, and height of the first electrode structures 21 can be adjusted according to the structural requirements of the target asymmetric nano-gap electrode 100, providing a spatial positioning reference and interface-induced region for subsequent selective organic molecule growth.

[0036] In one embodiment, the specific steps of patterning using nanoimprinting are as follows: after forming an imprinting adhesive layer on the surface of the substrate 10, the imprinting adhesive layer is imprinted and cured using a mold with a preset concave-convex structure. After removing the residual adhesive layer, a local area of ​​the substrate 10 is exposed. Then, the first electrode layer 20 is deposited and the imprinting adhesive layer is removed, thereby obtaining the patterned first electrode layer 20, which is beneficial to improving the large-area replication capability of the pattern.

[0037] In one specific embodiment, patterning can also be achieved using a shadow mask deposition method. Specifically, a mask with a preset opening pattern is disposed above the substrate 10, and a first metal material is deposited on the substrate 10 region corresponding to the opening of the mask using a metal deposition process. After removing the mask, the first electrode structure 21 is obtained. This method can reduce the impact of photoresist residue on the selective growth of organic molecules.

[0038] In this embodiment, the deposition method of the first electrode layer 20 and / or the second electrode layer 40 includes electron beam evaporation, thermal evaporation, magnetron sputtering, atomic layer deposition, or a combination thereof. The first electrode layer 20 and the second electrode layer 40 are made of different materials to form an asymmetric nanogap electrode 100.

[0039] In this embodiment, the materials of the first electrode layer 20 and the second electrode layer 40 are each independently selected from one or more of gold, silver, copper, aluminum, palladium, platinum, chromium, titanium, nickel, or their alloys, and the material of the second electrode layer 40 is different from that of the first electrode layer. In this embodiment, the material of the second electrode layer 40 is different from that of the first electrode layer 20 to form a self-aligned asymmetric nanogap electrode 100. By selecting metal materials with different work functions, electrochemical activities, catalytic activities, adsorption characteristics, or chemical stability as the first electrode layer 20 and the second electrode layer 40, asymmetric physicochemical boundaries can be formed on both sides of the nanogap 50, giving the nanogap 50 region a built-in potential difference, interfacial selectivity, or differentiated adsorption response, thereby facilitating functions such as rectification, selective transport, molecular recognition, gas sensing, or electrochemical response in the device. For example, the first electrode layer 20 and the second electrode layer 40 can respectively adopt different metal combinations such as Au / Al, Ag / Cu, and Au / Pd to adjust the electrode work function difference, surface reactivity, or adsorption capacity of the analyte molecule according to the requirements of the target device.

[0040] Furthermore, in this embodiment, the asymmetric nanogap electrode 100 utilizes the edge of the first electrode structure 21 as an induction reference for the selective growth of organic molecules, and defines the position of the second electrode structure 42 and the width of the nanogap 50 through the organic molecule selective region structure 30. Thus, the second electrode structure 42 can be self-aligned relative to the first electrode structure 21. Even if the first electrode layer 20 and the second electrode layer 40 are made of different materials, there is no need to introduce an additional high-precision overlay process, thereby reducing gap offset, short circuit, or open circuit problems caused by overlay deviations. This improves the yield, structural consistency, and large-area fabrication adaptability of the asymmetric nanogap electrode 100, while reducing process complexity and fabrication costs.

[0041] In this embodiment, before depositing the first electrode layer 20, an adhesion layer may be deposited on the surface of the substrate 10. The adhesion layer includes one or more of a chromium layer, a titanium layer, or a nickel layer. The adhesion layer is used to improve the bonding strength between the first electrode layer 20 and the substrate 10, and to prevent the first electrode structure 21 from falling off during subsequent cleaning, deposition, or ultrasonication.

[0042] In this embodiment, the thickness of the first electrode layer 20 is 5nm-50nm, and the thickness of the second electrode layer 40 is less than or equal to the thickness of the first electrode layer 20. The thickness of the first electrode layer 20 not only defines the conductivity and structural height of the first electrode structure 21, but also serves as a step height parameter during the selective growth of organic molecules. When the first electrode structure 21 has an appropriate height, organic molecules can form stable adsorption, nucleation, enrichment, or capillary spreading regions at the edge of the first electrode structure 21, allowing the selective organic molecule structure 30 to form a controllable lateral expansion size around the first electrode structure 21. This lateral expansion size further defines the spatial spacing between the second electrode layer 40 and the first electrode structure 21, thereby enabling the control of the width of the nano-gap 50. If the thickness of the first electrode layer 20 is too small, the step effect and interface induction at the edge of the first electrode structure 21 will be insufficient, and the enrichment boundary of organic molecules on its periphery will not be stable enough, which will easily lead to a decrease in the size uniformity of the nano-gap 50. If the thickness of the first electrode layer 20 is too large, the accumulation or spreading morphology of organic molecules at the edge may be excessively increased, resulting in a larger gap width or non-uniform structural boundary. Therefore, limiting the thickness of the first electrode layer 20 to the range of 5nm-50nm is beneficial to balance electrode continuity, interface induction ability and controllability of the nano-gap 50 size.

[0043] When the thickness of the second electrode layer 40 matches the thickness of the first electrode layer 20, the second electrode layer 40 can better replicate the deposition boundary defined by the organic molecule selected region structure 30. After ultrasonically removing the organic molecule selected region structure 30 and its surface second electrode layer 40, the second electrode layer 40 located on the surface of the substrate 10 is retained as the second electrode structure 42, thereby forming a nano-gap 50 with stable width and clear boundary between the first electrode structure 21 and the second electrode structure 42. Here, the thickness of the first electrode layer 20 can be 5nm, 10nm, 20nm, 30nm, 40nm, or 50nm, or any other value between 5nm and 50nm.

[0044] In this embodiment, after the formation of the first electrode layer 20 and before the deposition of organic molecules, the substrate 10 on which the first electrode layer 20 is formed is subjected to a cleaning treatment and / or a surface activation treatment. The cleaning treatment includes ultrasonic cleaning with acetone, ethanol and deionized water in sequence, and the surface activation treatment includes oxygen plasma treatment, ultraviolet ozone treatment, vacuum degassing treatment or a combination thereof, to improve the deposition quality of organic molecules.

[0045] In this embodiment, oxygen plasma treatment is used to remove organic residues from the surface of the substrate 10 and the surface of the first electrode structure 21, and to adjust the hydrophilicity / hydrophobicity or surface energy state of the substrate 10 surface, thereby improving the selective migration difference of organic molecules between the first electrode structure 21 and the substrate 10. Vacuum degassing treatment is used to remove water vapor and volatile impurities adsorbed on the surface of the substrate 10, so as to improve the stability and repeatability of the organic molecule deposition process.

[0046] In this embodiment, the ultrasonic treatment is carried out in a good solvent for organic molecules. The good solvent can dissolve or soften the organic molecule selected region structure 30, causing the second electrode layer 40 covering the surface of the organic molecule selected region structure 30 to lose support and be removed, thereby retaining the portion of the second electrode layer 40 deposited on the surface of the substrate 10 and located outside the organic molecule selected region structure 30 as the second electrode structure 42.

[0047] In some embodiments, ultrasonic treatment may be replaced by mechanical stripping, solvent immersion, solvent-assisted ultrasonic treatment, or a combination thereof. For smaller patterned structures, the organic molecular selected region structure 30 or its surface second electrode layer 40 may be pre-destroyed before ultrasonic treatment to allow the solvent to penetrate the interior of the organic molecular selected region structure 30, thereby improving the removal efficiency of the organic molecular selected region structure 30 and its surface second electrode layer 40.

[0048] In some embodiments, the ultrasonic treatment frequency is any value from 40kHz to 80kHz, the ultrasonic power is any value from 80W to 120W, and the ultrasonic treatment time is any value from 3min to 60min. That is, the ultrasonic treatment frequency is any value from 40kHz to 80kHz, which means the ultrasonic treatment frequency can be 40kHz, 50kHz, 60kHz, 70kHz, or 80kHz, or any other value within the range of 40kHz to 80kHz; the ultrasonic treatment power is any value from 80W to 120W, which means the ultrasonic treatment power can be 80W, 90W, 100W, 110W, or 120W, or any other value within the range of 80W to 120W; and the ultrasonic treatment time is any value from 3min to 60min, which means the ultrasonic treatment time can be 3min, 4min, 5min, 10min, 20min, 30min, 40min, 50min, or 60min, or any other value within the range of 3min to 60min. By controlling the frequency, power, and time of ultrasonic treatment within the aforementioned range, the organic molecular selective structure 30 can be effectively dissolved, swollen, or softened under the action of a good solvent of organic molecules. This facilitates the removal of the second electrode layer 40 on the surface of the organic molecular selective structure 30 along with the organic molecular selective structure 30, thereby exposing the nanoscale gap between the first electrode structure 21 and the second electrode structure 42. Simultaneously, the aforementioned ultrasonic parameters do not excessively damage the second electrode layer 40 deposited on the surface of the substrate 10, which helps maintain the integrity and adhesion stability of the second electrode structure 42, reducing the risk of detachment, warping, or edge damage to the second electrode structure 42.

[0049] In a further embodiment, the preset surface energy difference is 0.7 J / m. 2 -1.3J / m 2 Any one of the values, i.e., the preset surface energy difference, can be 0.7 J / m. 2 0.8J / m 2 0.9J / m 2 1.0J / m 2 1.1J / m 2 1.2J / m 2 Or 1.3J / m 2 It can also be 0.7 J / m 2 -1.3J / m 2Any other value within the range. By controlling the surface energy difference between the first electrode layer 20 and the substrate 10 within the above range, organic molecules can exhibit significantly different interfacial adsorption, wetting, and migration behaviors on the surface of the first electrode layer 20 and the surface of the substrate 10. This makes organic molecules more inclined to migrate, adsorb, nucleate, or accumulate towards the periphery of the first electrode structure 21 with higher surface energy during the deposition process, and less likely to form a non-selective continuous deposition layer on the surface of the substrate 10, thereby improving the formation stability and boundary clarity of the organic molecule selected region structure 30.

[0050] In other embodiments, if the surface energy difference is too small, the interface induction difference between the first electrode structure 21 and the substrate 10 for organic molecules is insufficient, and organic molecules are prone to random deposition or non-selective residue on the surface of the substrate 10, resulting in unclear boundaries of the selected area structure; if the surface energy difference is too large, organic molecules may be over-enriched or spread around the first electrode structure 21, causing the lateral expansion size of the selected area structure to deviate from the preset range.

[0051] In a further embodiment, the following steps are included before step S400: The substrate 10 and / or the organic molecular selected region structure 30 are pretreated, including at least one of surface cleaning treatment, plasma treatment, surface activation treatment or interface modification treatment.

[0052] By pretreating the substrate 10 and / or the organic molecular selective region structure 30 before the deposition of the second electrode layer 40, not only can organic residues, adsorbed water and weakly bound impurities on the surface of the exposed area of ​​the substrate 10 be removed, improving the nucleation uniformity, deposition continuity and adhesion strength of the second electrode layer 40 on the surface of the substrate 10, but also the risk of the second electrode layer 40 falling off the surface of the substrate 10 as a whole, warping or breaking during the subsequent ultrasonic treatment can be reduced, so that the remaining second electrode layer 40 can stably form the second electrode structure 42.

[0053] Furthermore, the aforementioned pretreatment can improve the interfacial bonding stability between the second electrode layer 40 and the substrate 10, while preventing the second electrode layer 40 covering the surface of the organic molecule selected region structure 30 from being pulled off from the second electrode layer 40 on the surface of the substrate 10 during the removal process. Therefore, after ultrasonic removal of the organic molecule selected region structure 30 and its surface second electrode layer 40, the portion of the second electrode layer 40 on the surface of the substrate 10 can be preserved more completely, thereby improving the integrity of the second electrode structure 42, the clarity of the nano-gap 50 boundaries, and the consistency of the nano-gap 50 width, ultimately improving the fabrication yield and structural reliability of the asymmetric nano-gap electrode 100.

[0054] In a preferred embodiment, when the organic molecule is N,N'-bis(1-naphthyl)-N,N'-diphenylbiphenyldiamine, its molecular structure has a large π-conjugated system, which can form a strong π-metal interaction with the surface of the first metal electrode structure 21, making it easier for it to adsorb and nucleate on the surface of the metal electrode and its edge region relative to the surface of the substrate 10, thereby improving the selectivity of selective growth and the edge enrichment stability.

[0055] In another preferred embodiment, when the organic molecule is a carbazole-quinoxaline derivative, it can exhibit high surface migration ability or fluidity at a preset temperature, and can migrate and spread to the edge of the first electrode structure 21 based on the wettability difference between the first electrode structure 21 and the substrate 10, thereby forming an organic molecule selected region structure 30 that covers or is adjacent to the periphery of the first electrode structure 21.

[0056] In a further embodiment, the preset temperature of the substrate 10 is any value between 30°C and 250°C. That is, the preset temperature of the substrate 10 and the temperature that needs to be maintained during the organic molecule deposition process can be 30°C, 35°C, 50°C, 100°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, or 250°C, or any other value between 30°C and 250°C. In this embodiment, by controlling the preset temperature of the substrate 10 within the range of 30°C to 250°C and maintaining this preset temperature during the organic molecule deposition process, the organic molecules can obtain appropriate surface migration ability after reaching the surface of the substrate 10, while maintaining their selective adsorption, nucleation, wetting, or enrichment ability on the periphery of the first electrode structure 21. By controlling the temperature range, organic molecules can exhibit significant differences in interfacial behavior between the surface of the substrate 10 and the surface of the first electrode structure 21. This makes it difficult for organic molecules to form a non-selective continuous film on the entire surface of the substrate 10. Instead, they tend to migrate to the periphery of the first electrode structure 21 and form a selected organic molecule structure 30, thereby providing a stable sacrificial confinement template for the subsequent formation of nano-gap 50.

[0057] Furthermore, when the substrate 10 is preset to a temperature range of 30°C to 250°C, it can accommodate the selective growth requirements of different types of organic molecules. For organic molecules that are in a liquid or high-mobility state at the preset temperature, this temperature range is conducive to their migration and spreading to the edge of the first electrode structure 21 based on wettability differences, and the formation of stable coating or adjacent structures.

[0058] In other embodiments, if the temperature of the substrate 10 is below 30°C, the surface diffusion ability of the corresponding organic molecules is insufficient, which easily leads to random deposition or local residues on the surface of the substrate 10, resulting in insufficient selected area growth and thus affecting the clarity of the nano-gap 50 boundary. If the temperature of the substrate 10 is above 250°C, the corresponding organic molecules may undergo excessive desorption, excessive flow, or uncontrolled lateral spreading, resulting in instability of the organic molecule selected area structure 30 boundary and causing the width of the nano-gap 50 to deviate from the preset range.

[0059] In a further embodiment, the deposition rate of organic molecules is any value between 0.01 nm / min and 10 nm / min. That is, the deposition rate of organic molecules can be 0.01 nm / min, 0.05 nm / min, 1 nm / min, 2 nm / min, 3 nm / min, 4 nm / min, 5 nm / min, or 10 nm / min, or any other value between 0.01 nm / min and 10 nm / min. This ensures that the number of organic molecules reaching the surface of the substrate 10 per unit time remains within a suitable range, allowing sufficient time for surface diffusion, migration, adsorption, nucleation, or enrichment of organic molecules after reaching the surface of the substrate 10. This improves the stability of selective growth of organic molecules on the periphery side of the first electrode structure 21. By controlling this deposition rate range, it is possible to avoid non-selective accumulation on the surface of the substrate 10 due to excessively rapid supply of organic molecules, and also to avoid increased molecular desorption on the thermal substrate 10 and increased time for selective molecular growth due to excessively slow supply of organic molecules. This is beneficial for forming a selective organic molecule structure 30 with clear boundaries, good continuity, and controllable lateral expansion size.

[0060] Furthermore, the deposition rate of organic molecules and the preset temperature of the substrate 10 jointly affect the surface residence time and lateral migration distance of organic molecules. When the deposition rate is in the range of 0.01 nm / min to 10 nm / min, organic molecules can undergo sufficient desorption or migration on the non-target substrate 10 region, and are preferentially adsorbed, pinned, nucleated, or enriched around the first electrode structure 21, so that the organic molecule selected region structure 30 can stably define the deposition boundary of the subsequent second electrode layer 40. Thus, after removing the organic molecule selected region structure 30 and the second electrode layer 40 on its surface, a nano-gap 50 with good width consistency can be formed between the first electrode structure 21 and the second electrode structure 42, improving the size controllability, fabrication repeatability, and structural yield of the asymmetric nano-gap electrode 100.

[0061] In some embodiments, when the organic molecule is N,N'-di(1-naphthyl)-N,N'-diphenylbiphenyldiamine, the temperature of the substrate 10 is any value between 130°C and 170°C, the deposition rate of N,N'-di(1-naphthyl)-N,N'-diphenylbiphenyldiamine is 1 nm / min to 5 nm / min, and the deposition thickness of the organic molecule is 10 nm to 40 nm, so that the formed organic molecule selected region structure 30 has a preset lateral expansion size of 10 nm to 100 nm. This enables the organic molecule to obtain appropriate surface diffusion ability during the deposition process, and preferentially adsorb, nucleate and enrich around the first electrode structure 21 by means of its π-conjugated structure and the π-metal interaction between it and the first metal electrode structure 21, thereby forming an organic molecule selected region structure 30 with a lateral expansion size of 10 nm to 100 nm. Here, the temperature of the substrate 10 can be 130℃, 140℃, 150℃, 160℃ or 170℃, or any other value between 130℃ and 170℃. The deposition rate can be 1nm / min, 2nm / min, 3nm / min, 4nm / min or 5nm / min, or any other value between 1nm / min and 5nm / min. The deposition thickness of the organic molecules can be 10nm, 20nm, 30nm or 40nm, or any other value between 10nm and 40nm.

[0062] In this embodiment, the Cr / Au first electrode structure 21 provides π-metal interaction sites and selected growth boundaries, the substrate 10 temperature provides appropriate desorption, diffusion and nucleation balance, the 20nm equivalent deposition thickness provides sufficient organic molecule supply, and the 10nm Al second electrode layer 40 is beneficial for subsequent ultrasonic removal of excess metal layers, thereby improving the boundary clarity and size consistency of the nano gaps 50.

[0063] In some embodiments, when the organic molecule is a carbazoquinoxaline derivative, the temperature of the substrate 10 is any value between 190°C and 250°C, the deposition rate of the carbazoquinoxaline derivative is any value between 0.01 nm / min and 10 nm / min, and the molecular weight of the organic molecule is any value between 300 and 1000.

[0064] In this embodiment, the 30nm Au first electrode structure 21 provides the basis for wettability difference and step height, the 190°C substrate temperature 10 enables DtCBQA molecules to have high surface migration ability, and the 10nm equivalent deposition thickness provides an appropriate amount of molecules and facilitates subsequent ultrasonic removal of excess metal layers, thereby improving the clarity of the nano gap 50 boundary, width consistency and preparation yield.

[0065] The present invention also provides an asymmetric nanogap electrode 100 prepared by the above-mentioned method.

[0066] The technical solution of this application will be further described below with reference to specific embodiments.

[0067] Example 1 Step S100: A silicon wafer is selected as the substrate 10. The substrate 10 is ultrasonically cleaned sequentially in acetone, ethanol, and deionized water for 10 minutes each time. Then, the cleaned silicon substrate 10 is subjected to oxygen plasma treatment at a power of 100W for 1 minute. Afterward, photoresist is spin-coated onto the surface of the substrate 10, followed by pre-baking, exposure, and development to form a striped hollow pattern on the photoresist film surface. Subsequently, 3nm thick metallic chromium and 5nm thick gold layers are alternately deposited in the corresponding areas of the striped hollow pattern to form the first electrode layer 20. After deposition, the sample is ultrasonically treated sequentially in acetone, ethanol, and deionized water for 10 minutes to remove the photoresist and retain the Cr / Au composite metal pattern on the surface of the substrate 10, thereby forming the first electrode layer 20. The first electrode layer 20 includes multiple spaced-apart first electrode structures 21, with a 1μm gap between adjacent striped first electrode structures 21. Step S200: The substrate 10 with the first electrode layer 20 is subjected to oxygen plasma treatment again at a power of 40W for 20s to further clean the exposed surface of the substrate 10 and the surface of the first electrode structure 21; then the sample is placed in an ultra-high vacuum organic semiconductor evaporator for degassing at 400℃. After the sample cools, the temperature of the substrate 10 is controlled at 150℃ and maintained, and N,N'-di(1-naphthyl)-N,N'-diphenylbiphenyldiamine is deposited at a deposition rate of 3nm / min to make its equivalent deposition thickness 20nm, so that N,N'-di(1-naphthyl)-N,N'-diphenylbiphenyldiamine undergoes selective adsorption, nucleation and enrichment on the periphery of the first electrode structure 21 to form an organic molecular selected region structure 30; Step S300: Deposit 5 nm of metallic chromium on the surface of the substrate 10 on which the organic molecular selected region structure 30 is formed to form a second electrode layer 40. The second electrode layer 40 covers the exposed surface of the substrate 10 and the surface of the organic molecular selected region structure 30, and is separated from the first electrode structure 21 by the organic molecular selected region structure 30. Step S400: The sample is placed in a good solvent of N,N'-bis(1-naphthyl)-N,N'-diphenylbiphenyldiamine and ultrasonically treated to remove the organic molecular selected region structure 30 and the second electrode layer 40 located on the surface of the organic molecular selected region structure 30, while retaining the second electrode layer 40 deposited on the surface of the substrate 10 as the second electrode structure 42, thereby forming a nano gap 50 with a width of 50 nm between the first electrode structure 21 and the second electrode structure 42, and obtaining the nano gap electrode 100.

[0068] Example 2 The only difference between Example 2 and Example 1 is that the spacing between two adjacent strip first electrode structures 21 is different, and the maximum spacing between two adjacent strip first electrode structures 21 is 2μm.

[0069] Example 3 Step S100: Select a silicon dioxide substrate 10 and ultrasonically clean it sequentially in acetone, ethanol, and deionized water for 10 minutes each time. Then, subject the cleaned substrate 10 to oxygen plasma treatment at a power of 100W for 1 minute. Afterward, form a hollow circular array pattern on the surface of the substrate 10 using photolithography, and deposit a 20nm thick aluminum layer as the first electrode layer 20 within the corresponding area of ​​the hollow pattern. After deposition, ultrasonically treat the sample sequentially in acetone, ethanol, and deionized water for 10 minutes to remove the photoresist and retain the aluminum pattern on the surface of the substrate 10, thereby forming the first electrode layer 20. Step S200: The substrate 10 with the first electrode layer 20 is subjected to oxygen plasma treatment at a power of 40W for 20s to further clean the surface of the substrate 10; subsequently, the sample is placed in a vacuum organic semiconductor evaporator for high-temperature degassing. After the sample cools, the temperature of the silicon dioxide substrate 10 is controlled at 220℃ and maintained, and a carbazole-quinoxaline derivative is deposited at a deposition rate of 1nm / min to achieve an equivalent deposition thickness of 10nm. As a result, the carbazole-quinoxaline derivative migrates, spreads, and accumulates around the first electrode structure 21 based on the wettability difference between the first electrode structure 21 and the substrate 10, forming an organic molecular selected region structure 30; Step S300: A 20 nm thick metallic chromium layer is deposited on the surface of the substrate 10 on which the organic molecular selected region structure 30 is formed as a second electrode layer 40. Step S400: The sample is placed in acetone, a good solvent of carbazole and quinoxaline derivatives, and subjected to ultrasonic treatment to remove the organic molecular selected region structure 30 and the chromium layer on the surface of the organic molecular selected region structure 30, while retaining the chromium layer deposited on the surface of the substrate 10 as the second electrode structure 42, thereby forming a nano gap 50 with a width of 80 nm between the first electrode structure 21 and the second electrode structure 42, and obtaining the nano gap electrode 100 structure.

[0070] Example 4 The only difference between Example 4 and Example 1 is that the first electrode structure 21 is a circular structure.

[0071] Comparative Example 1 The only difference between Comparative Example 1 and Example 2 is that the temperature of the substrate 10 was 120°C during the deposition of the organic molecular selected region structure 30.

[0072] Comparative Example 2 The only difference between Comparative Example 2 and Example 2 is that the temperature of the substrate 10 was 190°C during the deposition of the organic molecular selected region structure 30.

[0073] Comparative Example 3 The only difference between Comparative Example 3 and Example 3 is that the temperature of the substrate 10 is 180°C.

[0074] Comparative Example 4 The only difference between Comparative Example 4 and Example 3 is that the temperature of the substrate 10 was 260°C during the deposition of the organic molecular selected region structure 30.

[0075] Figure 4 This is a scanning electron microscope (SEM) image of the product obtained in step S100 of the preparation of the asymmetric nano-gap electrode according to Example 1 of the present invention. Figure 5 This is a scanning electron microscope (SEM) image of the product obtained in step S200 of the preparation of the asymmetric nano-gap electrode according to Example 1 of the present invention. Figure 6 This is a scanning electron microscope (SEM) image of the product obtained in step S300 of the preparation of the asymmetric nano-gap electrode according to Example 1 of the present invention. Figure 7 This is a scanning electron microscope image of the product obtained in step S400 of the preparation of the asymmetric nano-gap electrode according to Example 1 of the present invention. Figure 8 This is a partially enlarged scanning electron microscope (SEM) image of the second electrode layer after deposition according to Embodiment 1 of the present invention. Figure 9 This is an atomic force microscopy (AFM) image of the selected region structure of an organic molecule according to Example 2 of the present invention. Figure 10 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 1 of the present invention. Figure 11 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 2 of the present invention. Figure 12 This is an atomic force microscopy (AFM) image of the selected region structure of an organic molecule according to Example 3 of the present invention. Figure 13 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 3 of the present invention. Figure 14 This is an atomic force microscopy image of the selected region structure of an organic molecule according to Comparative Example 4 of the present invention. Figure 15 This is a scanning electron microscope image of the circular nano-gap electrode array prepared according to Example 4 of the present invention.

[0076] Scanning electron microscopy was used to observe the products obtained from each step of the preparation of the asymmetric nanogap electrode in Example 1, and the results were as follows: Figures 4 to 7 The results are shown; scanning electron microscopy was performed on the local structure after the deposition of the second electrode layer in Example 1, and the results are as follows. Figure 8 The results are shown below; atomic force microscopy was performed on the selected region structures of the organic molecules in Examples 2-3 and Comparative Examples 1-4, and the results are as follows: Figures 9 to 14The results are shown; scanning electron microscopy observation of the first electrode structure in Example 4 yielded the following results. Figure 15 The results are shown.

[0077] like Figures 4 to 7 As shown, the first electrode structure 21 formed after step S100 in Embodiment 1 is distributed in a strip-like pattern (refer to...). Figure 4 The extension directions of each first electrode structure 21 are consistent, and the pattern boundaries are relatively regular, indicating that the first electrode layer 20 can provide a stable spatial positioning reference for subsequent selective organic molecule growth. After step S200, it can be observed that the organic molecular material forms a continuously distributed organic molecular selective region structure 30 along the periphery of the first electrode structure 21, and the organic molecular selective region structure 30 has a certain lateral extension width L relative to the first electrode structure 21 (refer to...). Figure 5 This indicates that at a preset temperature, organic molecular materials can migrate and accumulate around the first electrode structure 21 based on the interface difference between the first electrode structure 21 and the substrate 10, rather than being non-selectively deposited on the entire surface of the substrate 10. After depositing the second electrode layer 40 in step S300, the cross-sectional view shows that the second electrode layer 40 covers the surface of the substrate 10 and the surface of the organic molecular selected region structure 30. The organic molecular selected region structure 30 forms a raised region with actual physical thickness around the first electrode structure 21 (see reference). Figure 6 This protruding region can serve as a sacrificial confinement template, providing spatial isolation for the deposition boundary of the second electrode layer 40. After removing the organic molecule selected region structure 30 and its surface second electrode layer 40 in step S400, a nano-gap is formed between the first electrode structure 21 and the second electrode structure 42, and the gap region can be observed to be distributed in a narrow line shape in the magnified image (see reference). Figure 7 This indicates that the lateral extension region of the organic molecular selected region structure 30 can be effectively transformed into the final nano-interstitial region.

[0078] like Figure 8 As shown, after the deposition of the second electrode layer 40, the region where the organic molecular selected region structure 30 is located exhibits a convex morphology in cross-section, with the second electrode layer 40 covering the convex structure and the surface of the substrate 10 regions on both sides. This morphology indicates that the organic molecular selected region structure 30 is not merely an interface modification layer, but rather a solid structure capable of forming isolation in both the thickness and lateral directions. The second electrode layer 40 forms a height difference and boundary transition region between the top of the organic molecular selected region structure 30 and the surface region of the substrate 10, which facilitates the subsequent removal of the organic molecular selected region structure 30 and the second electrode layer 40 on its surface using a good solvent and ultrasonic treatment, while retaining the second electrode layer 40 deposited on the surface of the substrate 10 as the second electrode structure 42.

[0079] In summary, Example 1 induces selective growth of organic molecules through the first electrode structure 21 and utilizes the organic molecule selective region structure 30 to define the deposition boundary of the second electrode layer 40, thereby transforming the lateral expansion size of the organic molecule selective region structure 30 into a nano-gap between the first electrode structure 21 and the second electrode structure 42. The results show that the preparation method of this application can achieve self-aligned formation of nano-gap, and the organic molecule selective region structure 30 simultaneously functions as a selective growth template, a spatial isolation template, and a sacrificial removal template during the process, which is beneficial for improving the boundary clarity, size controllability, and structural consistency of the nano-gap.

[0080] like Figure 9 As shown, in Example 2, the organic molecule selected region structure 30 is distributed in a strip-like pattern along the extension direction of the first electrode structure 21, and the substrate 10 regions between adjacent strips are relatively clear. This indicates that under the conditions of substrate 10 temperature, deposition rate, and equivalent deposition thickness in this example, organic molecules can preferentially migrate, adsorb, and nucleate towards the periphery of the first electrode structure 21, forming a selected region structure with clear boundaries and good continuity. This result shows that organic molecules with π-conjugated structures can utilize the difference in interfacial interactions between themselves and the metal first electrode structure 21 at appropriate temperatures to achieve selective enrichment relative to the substrate 10 region, thereby providing a stable confined template for subsequent deposition of the second electrode layer 40 and sacrificial removal.

[0081] like Figure 10 As shown, the strip boundaries of the organic molecule selected region structure 30 are relatively blurred, and there are uneven diffusion or non-selective residues in some areas. This indicates that when the temperature of the substrate 10 is low, the surface migration ability of the organic molecules after reaching the surface of the substrate 10 is insufficient, making it difficult for them to migrate sufficiently to the periphery of the first electrode structure 21 and form a stable enrichment boundary. In this case, the lateral expansion size and edge position of the organic molecule selected region structure 30 are difficult to control stably, which is not conducive to the subsequent formation of nano-gap 50 with uniform width.

[0082] like Figure 11 As shown, a certain banded structure can be observed, but many granular protrusions or local residues appear near the bands and in the substrate 10 region. This indicates that when the temperature is too high, organic molecules may undergo excessive desorption, local aggregation, or edge enrichment and instability, leading to a decrease in the continuity and boundary stability of the selected region structure. Therefore, for the N,N'-bis(1-naphthyl)-N,N'-diphenylbiphenyldiamine system, both excessively low and excessively high temperatures of the substrate 10 are not conducive to the formation of a stable organic molecule selected region structure 30. The temperature conditions used in Example 2 can achieve a good balance between molecular diffusion, nucleation, and edge enrichment.

[0083] like Figure 12As shown, in Example 3, the organic molecular selected region structure 30 forms a continuous and well-defined strip-shaped region along the periphery of the first electrode structure 21, and the substrate 10 regions between adjacent selected region structures are clearly distinguishable. This result indicates that, under the temperature conditions of Example 3, the carbazole-quinoxaline derivative can exhibit appropriate surface migration ability or fluidity, and migrate, spread, and accumulate towards the edge of the first electrode structure 21 based on the wettability difference between the first electrode structure 21 and the substrate 10, thereby forming an organic molecular selected region structure 30 that can serve as a sacrificial confinement template.

[0084] like Figure 13 As shown, the distribution of organic molecules on the surface of substrate 10 tends to be broadened or contiguous, and the selected region boundary on the periphery of the first electrode structure 21 is not clear enough. This indicates that under this temperature condition, a stable match cannot be formed between the flow, wetting, spreading, and edge pinning of organic molecules, making it difficult to control the local morphology and lateral expansion range of the organic molecule selected region structure 30. This result shows that for the carbazoloquinoxaline derivative system, the temperature of substrate 10 needs to be matched with its high mobility or flow state to obtain a selected region structure with clear boundaries.

[0085] like Figure 14 As shown, organic molecules exhibit significant granulation or island-like aggregation along the strip region, disrupting the continuous coating morphology. This indicates that excessively high temperatures can cause organic molecules to undergo excessive flow, dewetting, or secondary aggregation, making it difficult to maintain a continuous and stable selected organic molecule structure 30. This type of morphology can easily lead to local metal residues, irregular gap boundaries, or local short circuits during the subsequent deposition and ultrasonic removal of the second electrode layer 40, which is detrimental to the stable fabrication of the asymmetric nano-gap electrode 100.

[0086] like Figure 15 As shown, the first electrode structure 21 can also be a circular structure, that is, the first electrode layer 20 includes a plurality of circular first electrode structures 21 arranged in an array.

[0087] In summary, the organic molecule selected region structure 30 can play a sacrificial isolation and gap definition role during the deposition of the second electrode layer 40, and after subsequent removal, it can form a nano gap 50 between the first electrode structure 21 and the second electrode structure 42, thereby improving the controllability of the width of the nano gap 50, the clarity of the boundary and the structural consistency.

[0088] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0089] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for preparing an asymmetric nanogap electrode, characterized in that, Includes the following steps: A first electrode layer having multiple spaced first electrode structures is formed on a substrate, wherein each first electrode structure has a preset surface energy difference or a preset adsorption energy difference with the substrate surface. An organic molecule selected region structure with a preset lateral expansion size is formed on the periphery of the first electrode structure. The organic molecule selected region structure is formed by the migration and enrichment of organic molecule material deposited on the substrate surface to the periphery of the first electrode structure when the substrate is at a preset temperature. A second electrode layer is deposited on the surface of the substrate and the organic molecule selected region structure, the material of the second electrode layer being different from that of the first electrode layer; The second electrode layer and the organic molecule selected region structure on the surface of the organic molecule selected region structure are removed to form a nano gap between the second electrode structure and the first electrode structure, thereby preparing the asymmetric nano gap electrode with a nano gap width of 10nm-100nm. The second electrode structure is the portion of the second electrode layer located between the organic molecule selected region structures.

2. The method for preparing the asymmetric nanogap electrode according to claim 1, characterized in that, The preset surface energy difference is 0.7 J / m. 2 -1.3J / m 2 Any value among them.

3. The method for preparing the asymmetric nanogap electrode according to claim 1, characterized in that, The organic molecular material has at least one of the following: a non-planar molecular structure, a predetermined surface migration capability, or a predetermined wettability, and the adsorption stability or wettability of the organic molecule on the surface of the first electrode structure is higher than its adsorption stability or wettability on the substrate surface.

4. The method for preparing the asymmetric nanogap electrode according to claim 1, characterized in that, The preset temperature of the substrate is any value between 30℃ and 250℃.

5. The method for preparing the asymmetric nanogap electrode according to claim 4, characterized in that, The deposition rate of the organic molecules is any value between 0.01 nm / min and 10 nm / min.

6. The method for preparing the asymmetric nanogap electrode according to any one of claims 1-5, characterized in that, Prior to the step of depositing a second electrode layer on the surface of the substrate and the organic molecule selected region structure, the method further includes: The substrate and / or the organic molecule selected region structure are pretreated, and the pretreatment includes at least one of surface cleaning treatment, plasma treatment, surface activation treatment or interface modification treatment.

7. The asymmetric nanogap electrode prepared by the method according to any one of claims 1-6.